HUBUNGAN KARAKTERISTIK INDIVIDU DAN PENGAWASAN K3 DENGAN UNSAFE ACTION TENAGA KERJA BONGKAR MUAT - Datuh Inayah Dibyaguna Suryanto; Noeroel Widajati (Universitas Airlangga, 2017)
An unsafe action is a problematic behavior by a worker that deviates from workplace safety protocols or is not in accordance with workplace risk procedures. Accidents (80–85%) are caused by omission labor who demonstrate low compliance to the occupational safety and health in the workplace.The purpose of this research is to analyze the correlations for two sets of parameters related to unsafe loading-unloading labor practices in PT Pelabuhan Indonesia III Cabang Tanjung Perak individual characteristic and occupational safety and health supervision. A quantitive study with a cross sectionalapproach was conducted. In this study, primary data were obtained from questionnaires and observations in the workplace. Secondary data were obtained from the documents available on the PT Pelabuhan Indonesia III Cabang Tanjung Perak. Study respondents consisted of the loading-unloading workers in PT Pelabuhan Indonesia III Cabang Tanjung Perak. Respondents were obtained from simple random sampling technique, and 59 respondents were enrolled. This study analyzed individual characteristics and occupational safety and health supervision. Data were analyzed by using the Pearson’s correlation coefficient pearson with a linear significance of 0.05. Study results indicated that unsafe labor actions by labor occurred in the medium and heavy categories. The Pearson’s correlation coefficient indicated that unsafe actions correlated with age and occupational safety and health supervision, while insignificant variables related to unsafe actions included working time and level of education. Training-associated occupational safety and health also required enhanced knowledge about workplace dangers and unsafe actions at work. Especially to labor loading unloading whose aged 31-40 years old and had elementary school.Keywords: unsafe action, individual characteristic, occupational safety and health supervision